PENGARUH PRAKTEK TATA KELOLA PERUSAHAAN TERHADAP STRUKTUR MODAL - Dewi, Ni Komang Elsa; Dewi, Sayu Ketut Sutrisna (E-Jurnal Manajemen, 2018)
This research was conducted at a manufacturing company listed on the Indonesia Stock Exchange. The population used are all listed manufacturing companies respectively and disclose information about corporate governance practices in BEI period 2014-2016. Sample determination method used in this study is saturated sampling, with the number of samples obtained 40 companies. Data analysis used is multiple linear regression test. Based on the results of this research analysis found that the size of the board of directors and institutional ownership have a positive and significant effect on capital structure. Another variable that is independent commissioner has positive and insignificant effect on capital structure and managerial ownership have negative and not significant significant to capital structure. This suggests that the more existing board of directors in the company will improve monitoring of management performance, it also applies to the increase of institutional ownership.   Keywords : capital structure, corporate governance, manufacturing company